Mathematical Modeling of Structural Integrity on High Rise Building Using Parallel Axis Theorem and Finite Element Analysis - Salim, Mohd Azli (ICOCI Publisher, 2011)
This  study  provides  an  introduction  to  the  concepts  and  principles  of  seismic  design,  including strategies  for  designing  earthquakeresistant  buildings  to  ensure  the  health,  safety,  and  security  of building  occupants  and  assets.  There  are  three  main  factors  that  contribute  to  the  successful  seismic design.  Firstly,  the  design  team  must  consider  a  multihazard  approach  in  designing  the  structure  that accounts for the potential impacts of seismic forces as well as all the major hazards to which an area is vulnerable.  Secondly,  considerations  need  to  be  made  pertaining  to  the  performancebased requirements.  This  requirement  may  exceed  the  minimum  life  safety  requirements  of  current  seismic codes.  Therefore,  the  safety  factor  must  be  established  to  respond  appropriately  to  the  threats  and risks  posed  by  natural  hazards  on  the  building's  mission  and  occupants.  Thirdly,  since  earthquake forces are  dynamic  and  each  building  responds according  to  its  own design  complexity,  it  is  essential that the design team work collaboratively and have a common understanding of the terms and methods used  in  the  seismic  design  process.  In  addition  to  that,  as  a  general rule,  building  that  is  designed  to resist earthquakes should also resist blast (terrorism) or wind, suffering less damage.